Linguistic purism and language criticism in German - Schwinn, Horst (Handbuch europäische Sprachkritik online, 2018)
Linguistic purism is a form of language criticism. Its primary objective is to ‘keep the language pure’. Keeping the language pure first of all refers to the rejection of foreign-language influences, especially in lexis, but attempts to develop a norm as well as the advancement of a standard or national language are also part of linguistic purism. Linguistic purism can be promoted by individuals as well as by institutions. First attempts at trying to keep the German language pure date back to language societies in the 17th century. From a diachronic perspective, purism has focused on different aspects of language and its usage. What all puristic efforts have in common is that they are usually linked to a rise in national sentiment. Despite institutional efforts - and contrary to other languages - purism is not part of the German language policy and thus not government-controlled.
Gesehen am 07.07.2020